2005
DOI: 10.1590/s1516-89132005000100007
|View full text |Cite
|
Sign up to set email alerts
|

Central venous access through the external jugular vein in children submitted to bone marrow transplantation

Abstract: Establishment of long-term central venous access is a sine qua non step for bone marrow transplantation in children. Most frequently, long-term central venous access has been obtained via blind percutaneous cannulation of subclavian and internal jugular veins or via internal jugular vein cutdown. In order to avoid some potential minor and major complications associated with the subclavian or internal jugular approaches, the authors describe an easy, simple and safe method for central venous access through an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
4
0
2
Order By: Relevance
“…In a study of 100 children after HSCT, it was observed that 80 had their catheters successfully implanted in the right or left external jugular, with dissection, which made the technique simple and safe. In this case, the preferred site for CVC implantation was the subclavian vein (76%), which associated to Hickman, provides more comfort to patients who stay for long periods with catheters, alternating between hospitalizations for chemotherapy and home recovery 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of 100 children after HSCT, it was observed that 80 had their catheters successfully implanted in the right or left external jugular, with dissection, which made the technique simple and safe. In this case, the preferred site for CVC implantation was the subclavian vein (76%), which associated to Hickman, provides more comfort to patients who stay for long periods with catheters, alternating between hospitalizations for chemotherapy and home recovery 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The longest length of stay was 279 days with a Hickman catheter, which corroborates a comparative study with implants of the same model, which showed an average length of stay of 41.4 days, ranging from 0 to 118 days of stay. The risk of infection is higher in the first 90 days of implantation 1 , 16 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…7 hastada ise oluşan fibrin kılıfın damar çapını daralttığı görüldü. (5)(6)(7) . Açık cerrahinin asıl sorun olan önemli sonucu ise işlem yapılan damarların yaklaşık %33'ünde daha sonra oklüzyon gelişmesidir (8) .…”
Section: Bulgularunclassified
“…The Seldinger technique (in its original or modified version) is the most used (3)(4) . The subclavian vein is the first choice when a central venous access is indicated, as it is the place with the smallest risk of catheter-related thrombosis and infection in comparison with the femoral and internal jugular vein (5) .…”
Section: Introductionmentioning
confidence: 99%